The role of photorespiration in plant immunity - Jiang, Xiaotong; Walker, Berkley J.; He, Sheng Yang; Hu, Jianping (Frontiers in Plant Science, 2023)
To defend themselves in the face of biotic stresses, plants employ a sophisticated immune system that requires the coordination of other biological and metabolic pathways. Photorespiration, a byproduct pathway of oxygenic photosynthesis that spans multiple cellular compartments and links primary metabolisms, plays important roles in defense responses. Hydrogen peroxide, whose homeostasis is strongly impacted by photorespiration, is a crucial signaling molecule in plant immunity. Photorespiratory metabolites, interaction between photorespiration and defense hormone biosynthesis, and other mechanisms, are also implicated. An improved understanding of the relationship between plant immunity and photorespiration may provide a much-needed knowledge basis for crop engineering to maximize photosynthesis without negative tradeoffs in plant immunity, especially because the photorespiratory pathway has become a major target for genetic engineering with the goal to increase photosynthetic efficiency.